PRACTICE OF THE INSTITUTE OF BUSINESS OMBUDSMAN OF UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article describes in detail the experience and practical significance of the Business Ombudsman of Uzbekistan in the field of protecting the rights of entrepreneurs, the stage of development of the institution, the powers of the Business Ombudsman and the results achieved since the date of formation.